Comparison of Learning Outcomes and Student Activeness in the Use of Guided Inquiry Learning Model with Media e-Module, Learning Videos, and Textbooks - Lapele, Dina Amalya (Jurnal Pendidikan Matematika, 2023)
Various learning media and models are used to improve learning outcomes and student activities. Current learning emphasizes student activity to achieve good learning outcomes. This research is a descriptive qualitative research that aims to describe the comparison of learning outcomes and student activities in three classes that use the Guided Inquiry learning model with different learning media. The first class uses module media, the second class uses learning video media, and the third class uses textbooks. The subjects of this study were students of the Mathematics Education Study Program at IAIN Ambon who took Differential Calculus, Introduction to Basic Mathematics, and Ordinary Differential Equations courses. Data collection techniques used are tests and observations. The data analysis technique used is data reduction, data presentation, and making conclusions. The results of the study proved that the highest learning outcomes were classes that used Guided Inquiry learning model with module media, then classes that used visual learning media, and classes that used textbook media. The best active learning is in classes that use Guided Inquiry learning model with learning videos media, then classes that use textbook media, and classes that use module media